2005
DOI: 10.1038/modpathol.3800292
|View full text |Cite
|
Sign up to set email alerts
|

Distinct spatial expression patterns of AP-2alpha and AP-2gamma in non-neoplastic human breast and breast cancer

Abstract: Although transcription factors AP-2alpha and AP-2gamma have been implicated in the control of estrogen receptor (ER) and ErbB-2, their impact for breast cancer is still controversial. To better understand the role of AP-2 proteins in mammary neoplasia, the analysis of their spatial expression pattern in normal breast and breast cancer is required. A total of 51 specimens of female breast cancer patients and a tissue microarray containing 93 additional female breast cancer cases were immunohistochemically stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 23 publications
6
76
1
Order By: Relevance
“…Except for the breast, none of these control tissues showed positive staining for AP-2g. As described, 15 outer myoepithelial cells of normal ductuli lactiferi were immunopositive as were ductal invasive adenocarcinomas of the breast. Hence, AP-2g is not exclusively expressed in GCTs but can also be found in some tumors derived from somatic tissues.…”
Section: Distribution Of Ap-2 Immunostaining In Testicular Controls Amentioning
confidence: 64%
See 1 more Smart Citation
“…Except for the breast, none of these control tissues showed positive staining for AP-2g. As described, 15 outer myoepithelial cells of normal ductuli lactiferi were immunopositive as were ductal invasive adenocarcinomas of the breast. Hence, AP-2g is not exclusively expressed in GCTs but can also be found in some tumors derived from somatic tissues.…”
Section: Distribution Of Ap-2 Immunostaining In Testicular Controls Amentioning
confidence: 64%
“…15 Briefly, dewaxed tissue sections were microwave-pretreated prior to incubation with primary antibody. Sections were incubated overnight at 48C with a polyclonal rabbit anti-AP-2g antibody (1:500, H77; Santa Cruz Biotechnology, Heidelberg, Germany).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…63 In immunohistochemical studies using a large number of patient samples, Pellikainen et al 14 observed that the HER-2 2 /AP-2 1 patients had the best prognosis for recurrence-free survival while the worst prognosis was seen with HER-2 1 /AP-2 2 patients. In related studies, Friedrichs et al 64 observed distinct patterns of AP-2a and AP-2g spatial expression in nonneoplastic breast and breast cancer. Moreover, high expression of AP-2a correlated with high ER expression, better differentiation, and better survival of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies using different polyclonal AP-2γ antibodies failed to find a link with outcome. One study focused on patients with early-stage disease treated with lumpectomy [15] and in the second study the commercial antibody employed apparently only stained the myoepithelial compartment [37]. In contrast, using gene expression profiling, TFAP2C mRNA expression was associated with advancing clinical grade (p < 0.002 [17]).…”
Section: Discussionmentioning
confidence: 99%